2013 International Conference on Mechatronics, Electronics and Automotive Engineering 2013
DOI: 10.1109/icmeae.2013.33
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Software Processes Improvement Needs in SMEs

Abstract: Nowadays in the software development environment SMEs occupies a considerable percentage of the number of companies. SME's generate the 52% of the gross domestic product of the countries and around 72% of the formal employees. For this reason, it is important to guarantee the quality of SME´s products improving the quality of processes used to develop them. However, SMEs suffer lack of implementation of formal processes for the software development. This paper shows the research results that aim to establish a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 2 publications
0
12
0
2
Order By: Relevance
“…With considerations to resources [9], [23], [36], metric selection methods [3], infrastructure facilities, team size [8], and a well-planned software measurement program [23], [36], process metrics can assist SMEs in measuring and improving their process performance.…”
Section: Background a Process Metrics For Software Developmentmentioning
confidence: 99%
“…With considerations to resources [9], [23], [36], metric selection methods [3], infrastructure facilities, team size [8], and a well-planned software measurement program [23], [36], process metrics can assist SMEs in measuring and improving their process performance.…”
Section: Background a Process Metrics For Software Developmentmentioning
confidence: 99%
“…Habib in his work stated that management support, communication, organizational culture, staff experience, participation and training, resources, clear and relevant SPI goals, program reviews, software engineering tools and technology, and process ownership are the factors, which measure the success of SPI initiatives. Claudia et al performed a review to describe the features of the software development SMEs to identify the needs towards SPI implementation initiatives. Moreno‐Campos et al concluded in their work that considering the large percentage of software SMEs across the world, relatively very few studies have focused on real processes that they are using in everyday software activities.…”
Section: Related Workmentioning
confidence: 99%
“…Researchers suggest that only about 7% of SSCs in practice have adopted software process improvement (SPI) standards and models [12]. Additionally, software development practice in SSCs faces a myriad of challenges [13], [14] to the extent that about 50-60 percent of software projects either partially or totally fail. However, other studies report a higher failure rate; for example, in 2018, the project failure rate was reported at 70 percent [15].…”
Section: Introductionmentioning
confidence: 99%